The role of tqm and agile leadership in improving teacher performance: a study on madrasah aliyah in South Kalimantan - Syaifullah Syaifullah; Ria Mardiana Yusuf; Ami Pujiwati; Zainur Hidayah (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Madrasah Aliyah plays a crucial role in shaping future generations, but improving teacher performance remains a significant challenge. The application of Total Quality Management (TQM) and agile leadership is a strategic approach to enhancing educational quality. TQM emphasizes continuous improvement, while agile leadership promotes flexibility and adaptation in response to educational changes. This study explores how TQM and agile leadership work together to improve teacher performance in State Aliyah Madrasahs (MAN) in South Kalimantan. The goal is to analyze the impact of TQM and agile leadership on teacher performance and examine the role of TQM in strengthening the relationship between leadership agility and teacher performance. Using a mixed methods approach, the study examines the interplay of TQM, leadership agility, teacher training, and performance in 13 South Kalimantan MAN schools. A sample of 303 teachers participated, with quantitative data analyzed using PLS-SEM and qualitative data from interviews and focus group discussions. The qualitative data helped validate and enrich the quantitative findings, providing deeper insights into the factors affecting teacher performance. The results show that both leadership agility and teacher training positively influence teacher performance, with TQM moderating the relationship between leadership agility and performance. To improve teacher performance, steps such as fostering a culture of continuous improvement through workshops and feedback, integrating TQM principles into training, and promoting agile leadership focused on collaboration and problem-solving can create a supportive environment that enhances teacher performance and student outcomes.